Large‐magnitude Pelvic and Retroperitoneal Tissue Damage Predicts Organ Failure. Issue 6 (June 2016) - Gaski, Greg; Frantz, Travis; Steenburg, Scott; Bell, Teresa; McKinley, Todd
Abstract: Background: Pelvic and retroperitoneal trauma is a major cause of morbidity and mortality in multiply injured patients. The Injury Severity Score (ISS) has been criticized for underrepresenting and inaccurately defining mechanical injury. The influence of pelvic injury volume on organ dysfunction and multiple organ failure (MOF) has not been described. Through the use of CT, this investigation sought to precisely define volumes of mechanical tissue damage by anatomic region and examine its impact on organ failure. Questions/purposes: (1) Do patients with MOF have a greater volume of pelvic and retroperitoneal tissue damage when compared with those without MOF? (2) In patients who sustained pelvic trauma, does the magnitude of pelvic injury differ in patients with MOF? (3) Does the magnitude of organ dysfunction correlate with pelvic tissue damage volume? Methods: Seventy‐four multiply injured patients aged 18 to 65 years with an ISS ≥ 18 admitted to the intensive care unit for a minimum of 6 days with complete admission CT scans were analyzed. Each identifiable injury in the head/neck, chest, abdomen, and pelvis underwent volumetric determination using CT to generate regional tissue damage volume scores. Primary outcomes were the development of MOF as measured by the Denver MOF score and the degree of organ dysfunction by utilization of the Sequential Organ Failure Assessment (SOFA) score. Mean pelvic and retroperitoneal tissue damage volumes were compared in patients who developed MOF and those who did not develop MOF using Student's t‐test. Among patients who sustained pelvic injuries, we compared mean volume of tissue damaged in patients who developed MOF and those who did not. We assessed whether there was a correlation between organ dysfunction, as measured by the SOFA score as a continuous variable, and the volume of pelvic and retroperitoneal tissue damage using the Pearson product‐moment correlation coefficient. Results: The average volume of tissue damage was greater in patients with MOF when compared with those without (MOF: 685.667 ± 1081.344; non‐MOF: 195.511 ± 381.436; mean difference 490.156 cc [95% confidence interval CI, 50.076‐930.237 cc], p = 0.030). Among patients who sustained pelvic injuries, those with MOF had higher average tissue damage volumes than those without MOF (MOF: 1322.000 ± 1197.050; non‐MOF: 382.750 ± 465.005; mean difference 939.250 [95% CI, 229.267‐1649.233], p = 0.013). Organ dysfunction (SOFA score) correlated with higher volumes of pelvic tissue damage (r = 0.570, p < 0.001). Conclusions: This investigation demonstrated that greater degrees of pelvic and retroperitoneal tissue damage calculated from injury CT scans in multiply injured patients is associated with more severe organ dysfunction and an increased risk of developing MOF. Early identification of polytrauma patients at risk of MOF allows clinicians to implement appropriate resuscitative strategies early in the disease course. Improved stratification of injury severity and a patient's anticipated clinical course may aid in the planning and execution of staged orthopaedic interventions. Future avenues of study should incorporate the ischemic/hypoperfusion component of pelvic injury in conjunction with the mechanical component presented here for improved stratification of multiply injured patients at higher risk of MOF. Level of Evidence: Level III, prognostic study.